PROBLEMS OF RESOLVING DOMAIN DISPUTES: INTERNATIONAL PRACTICE - Yurovska, Galyna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of this article is to clarify the main problems of resolving domain disputes in international arbitration using the UDRP procedure and to provide suggestions for their improvement. To this end, the administrative procedure for considering domain disputes under the UDRP on the Internet was analyzed and its disadvantages and advantages compared to judicial proceedings were described. Based on the results of the study, proposals were formulated to improve the procedure for considering domain disputes. The methodological basis of the study is general scientific and special methods of cognition. The use of these methods made it possible to describe problematic issues regarding the resolution of domain disputes in international arbitration. Results: in order to improve the administrative procedure for reviewing domain name disputes under the UDRP and minimize its shortcomings, it seems advisable to introduce mechanisms for compensation for damage when reviewing domain name disputes under the UDRP procedure, for example, in the form of reimbursement by the defendant of a one-time compensation in the amount of legal costs incurred by the plaintiff. Discussion: in the context of the threat of cybersquatters, the UDRP administrative procedure has a number of advantages over litigation. First, it is contractual and does not depend on the location and national jurisdiction of the parties, while in litigation there may be difficulties in finding and identifying the defendant. Secondly, the complaint filing system with some arbitration centers greatly simplifies the filing procedure, as the websites have developed examples of model complaints and model responses to complaints. In addition, the absence of a requirement that a lawyer represent the plaintiff or defendant greatly facilitates access to the procedure. Third, the panel of appeals is represented by professional lawyers with significant experience in international domain name and trademark disputes. Fourth, the UDRP procedure is fast and usually takes about two months. Fifth, the UDRP practice is unified and predictable, as it is based on precedents. The publication of such precedents in the public domain, in turn, provides an opportunity to predict the practice of panels and future decisions. Sixth, the UDRP procedure does not “compete” with the judicial protection of individual rights.